Comparative Analysis of the Treatment of the Alcestis-Stuff by Euripides and by Wilder - Franz-Rudolf Herber (European Scientific Journal, ESJ, 2024)
This is the starting point of the following analysis: Life and death belong indissolubly together, but nobody of us knows what is waiting for us when we will have died. According to Christian religion the dead shall resurrect again and start immediately into an eternal life full of happiness in an unknown atmosphere without any sorrows and any problems to overcome. The ancient writers, that lived before Jesus Christ, had at hand an underworld as the realm of that god that is responsible for death. In very rare and exceptional cases a very deserved dead is given the allowance to enter again into his former earthen life. This procedure of bringing a dead person back to life might be a kind of deal between deities and mankind in this way that another person had to die and then to live in the underworld instead of the doomed person. This stuff is a subject-matter of legends, fairy tales and finally of classical drama. The heroes of the drama are Admetus and Alcestis – a royal couple; Admetus is doomed to death and his wife Alcestis wants to die instead of her husband. This treatise is written by an author who is as well a lawyer as a philologist. The treatise uses modern methods of literary comparison, that the author did learn at the examples of ancient texts and modern texts at the Faculty of Philosophy of the University of Saarland (Germany). The comparison between the Euripides-version and the Wilder-version is not an end in itself, the comparison aims to show the given literary differences based on the history of the development of the Alcestis-stuff in the light of the fact that the ancient text is the source for the modern text. Thus it becomes once more clear that the texts of old Greek authors do live on in a figurative sense until modern times. Wilder himself is a modern American author who consciously sought connection to antiquity, also because he did go through very intensive university courses in archaeology. This connection to ancient Greek literature, of course, makes modern American literature very attractive for European readers and for readers from other areas of the world.